Bridging healthcare gaps through specialized mobile healthcare services to improve healthcare access and outcomes in rural Hungary - Mark Virag; Rita Kovacs; Gergely Marovics; Luca Toth; Barbara Sandor; Peter Voros; Veronika Gyori–Dani; Ferenc Nagy; Daniel Eorsi; Janos Sandor; Istvan Kiss; Ferenc Vincze; et al. (Scientific Reports)
Abstract Telemedicine offers promising solutions to healthcare challenges in underserved rural areas. This study evaluates a public insurance-based telemedicine system implemented in Hungary, where 12 Mobile Healthcare Service Centers (MHSCs) provided general and specialist care to over 21,000 residents across five rural districts. During the six-month study period, 1,889 individuals received medical care through 4,118 healthcare events. The intervention led to the identification of 105 new hypertension cases and 26 new diabetes cases. Patient feedback was overwhelmingly positive, with 96% willing to recommend the service, and nearly all doctors expressing a willingness to continue participation. A 10% reduction in relative referral rates was observed, suggesting that the system helped alleviate pressure on traditional healthcare providers. Additionally, 2,026 screenings, 1,572 chronic care visits, and 151 laboratory tests were conducted, demonstrating the broad utilization of the service. The estimated monthly operational cost of the telemedicine system was approximately $250,000, which exceeded the national primary healthcare funding of $160,000 per month, highlighting the financial implications of scaling similar programs. The findings indicate that mobile telemedicine services can improve healthcare accessibility in underserved areas and reduce healthcare disparities. Further research is needed to assess the long-term effects of such interventions.